Evaluating point of care testing for glycosylated haemoglobin in primary care facilities in the Western Cape - Ugoagwu, Abimbola A. (Stellenbosch : Stellenbosch University, 2017)
Introduction: Diabetes Mellitus makes a significant contribution to the burden of disease in South Africa. Monitoring of glycaemic control with HbA1c is imperative in the management of diabetes. Presently, there are no facilities for point of care testing for HbA1c in Western Cape and there are concerns about the cost, feasibility and technical quality of point of care testing. Aims and objectives: The study aimed at evaluating the costs and consequences for quality of care of introducing point of care testing for HbA1c in patients with diabetes at community health centres in the Western Cape. Methods: This was a quasi-experimental study with four community health care centres, two matched control sites and two intervention sites. A point of care testing machine for HbA1c was introduced to the intervention sites for 12 months. Patients were randomly selected from the diabetes register in the intervention (N=150) and control sites (N=151) respectively and data collected from patient records. Focus group interviews were done at the intervention sites. Technical quality and cost implications were also evaluated. Results: Point of care testing for HbA1c in primary health care was feasible and resulted in more immediate feedback to the patients about their level of control (p<0.05). The point of care group had better glycaemic control (p=0.02) though this needs further follow up. Point of care testing did not lead to any change in the frequency of testing or change in clinical practice. Cost analysis showed that R824.33 was saved per 100 tests by using the point of care testing machine when compared with laboratory testing for the same number of tests. Conclusion: The study demonstrated the feasibility of introducing point of care testing for HbA1c in primary care. Point of care testing resulted in more immediate feedback of results to the patient and possibly better glycaemic control. It however did not lead to change in clinical practice and patient education. The technical quality compared favourably with laboratory testing for HbA1c.